An evaluation of the Financial Sector Charter and the Community Reinvestment Bill and their implications on the delivery of low income housing finance in South Africa. - Nyandoro, Edith (My University, 2009)
This research report is an account of the results of investigations into the critical analysis of the private sector’s Financial Sector Charter (FSC) and the government’s Community Reinvestment Bill (CRB) in comparing their anticipated advantages towards housing and housing finance for the low income sector in South Africa. 2 stages of data gathering were adopted; namely interviews with 5 Banking Council officials and 5 Ministry of Housing officials and a questionnaire survey with representatives from SACC, NALEDI, SANGOCO, COSATU and SANCO which are independent organizations, which amongst other duties, generally assist in serving the social needs of disadvantaged individuals in the society. Multi-criteria analysis and SWOT analysis techniques were used to analyse the qualitative data. Results showed that the most critical aspect of the FSC is the establishment of risk sharing responsibilities between the government and the private sector, which still needs to be resolved. The private sector views the CRB as a forceful mechanism with strict requirements, which would result in the private sector’s participation in provision of housing finance to the low income sector to be ineffective as they would be acting unwillingly. Independent organizations view the CRB as being lenient on the private sector. Evaluation of the CRB and FSC showed that ultimate success lies in the combined efforts between the government and private sector, which in turn lies in the settling of the Memorandum of Understanding on-going negotiations. Key recommendations for addressing the low income sector housing and housing finance problems include; cultural adjustment of the banks towards low income sector individuals, formation of partnerships in dealing with housing and housing finance problems, establishment of efficient secondary property markets through amenities provision and infrastructure upgrading, identification of effective default management models, accommodation of new intellectual ideas and provision of different mortgage securities by banks and the government.
Keywords: Housing; Housing finance; Low income sector; Private sector